Impact of E-Banking on Operational Efficiency of Employees in Nepalese Commercial Banks - Adhikari, Shankar Nath; Mahat, Kushendra B (Journal of Advanced Academic Research, 2023)
This study investigates the influence of electronic banking methods, including ATMs, mobile banking and internet banking on the operational efficiency of employees in Nepalese commercial banks. This research focuses on its implications in Nepal, aiming to understand how the adoption of digital technologies affects the day-to-day tasks, workload distribution, and overall performance of bank personnel. Mixed-methods approach involving surveys and interviews, the study analyzes employee perceptions and experiences, shedding light on the extent to which e-banking optimizes processes, improves customer interactions, and necessitates skillset adaptations. The findings of this research contribute valuable insights to academia and the banking industry, offering actionable information to enhance the benefits of e-banking while mitigating potential drawbacks on employee performance. By comprehensively exploring the relationship between e-banking and operational efficiency in Nepal's banking, this study equips stakeholders with knowledge crucial for strategic decision-making and sustainable growth within the evolving financial technology.